“A Study On Determinants Of Customer Perception & Factors Driving Customer Satisfaction In Cellular Phone Industry & Service Providers” (Journal of Namibian Studies : History Politics Culture, 2023)
Purpose: The stellar intention of the present research work is to know how far the moderate variables impact on the study of cell phone user perception towards service quality among telecom service providers. Further, the study conducted to probe factors driving customer satisfaction in cellular phone industry, and factors determining the choice of cell phone service providers and respondents level of perception on cellular service providers. Connectivity with everyone is crucial in today’s cyber world and mobile service is one among them. Cellular phone service providers should understand the innovative needs of consumer connectivity.Design / Approach: A well designed questionnaire which was previously known was administered properly to gather the required data. The respondents were interviewed in their workplace and personally the researcher conducted interview to collect the necessary data. Interview method aims at collecting data with more confidence, truthful and useful as the interviewer establishes more intimacy with respondents after clarifying objectives of the study.Findings: The study reveals that socio economic characteristics are impacting on the study on cell phone users perception towards service quality among telecom service providers with high degree of relationship. Further, the study reveals that factors like price sensitiveness, internet connection and good voice quality are driving customer satisfaction in cellular phone industry. Factors deciding the choice of cell phone service providers includes service quality, call quality and new technology use. Further, the study also found about the level of perception on cellular service providers and they include cost of living is increasing day by day, the new technology enhances demand and spending and lowers are not enough to cover the whole area etc.